ChemInform Abstract: A New Organocatalytic Concept for Asymmetric α‐Alkylation of Aldehydes. Issue 23 (June 2015) - Caruana, Lorenzo; Kniep, Florian; Johansen, Tore Kiilerich; Poulsen, Pernille H.; Joergensen, Karl Anker
Abstract Enamine‐activated aldehydes are added to p‐quinone methides to yield aldehydes with two contiguous stereocenters with good diastereo‐ and excellent enantioselectivity.